The Impact of a Structured Social Workshop on Risk Behaviors and Mood Regulation - Al-Dossary, Saeed Abdullah; Atak, Irmak; Atapour, Neda (Journal of Personality and Psychosomatic Research (JPPR), 2024)
This study aimed to evaluate the effectiveness of a Social Connectedness Workshop in mitigating risk-taking behaviors and improving mood regulation among adults experiencing mild to moderate levels of social disconnection. It hypothesized that increased social connectedness through structured intervention would lead to significant improvements in these psychological domains. A randomized controlled trial was conducted with 30 participants, aged 18-45, who were assigned to either an 8-session Social Connectedness Workshop (experimental group) or a control group receiving no intervention. Assessments using the Balloon Analogue Risk Task (BART) for risk-taking behaviors and the Difficulties in Emotion Regulation Scale (DERS) for mood regulation were conducted at baseline, post-intervention, and at a three-month follow-up. Data analysis was performed with SPSS-27, employing Analysis of Variance with repeated measurements and Bonferroni post-hoc tests. Participants in the experimental group showed significant reductions in risk-taking behaviors, with mean scores decreasing from 43.99 (SD = 5.44) at baseline to 37.39 (SD = 6.99) at follow-up (p < 0.01). Mood regulation also improved significantly, with mean scores increasing from 82.99 (SD = 13.77) to 90.49 (SD = 13.55) in the same group (p < 0.01). No significant changes were observed in the control group across both variables. The intervention group’s results displayed significant time, group, and interaction effects, indicating the workshop’s effectiveness in achieving the study’s objectives. The Social Connectedness Workshop effectively reduced risk-taking behaviors and enhanced mood regulation among participants, underscoring the importance of social ties and emotional support in psychological well-being. These findings suggest that structured social connectedness interventions can be a valuable component of mental health strategies aimed at reducing risk-taking behaviors and improving mood regulation.